Pengaruh Pembelajaran Diferensiasi Gaya Belajar Melalui Model Pembelajaran Project Based Learning Terhadap Hasil Belajar Matematika Kelas IV di Sekolah Dasar Negeri Gugus “Harati” Kecamatan Kahayan Hilir Kabupaten Pulang Pisau Tahun Pelajaran 2024/2025 - Yuliani, Yuliani; Debora, Debora; U.Z. Mikdar (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
This study investigates the impact of differentiated learning styles through Project-Based Learning (PBL) on mathematics achievement among fourth-grade students in Harati Public Elementary School Cluster, Kahayan Hilir Subdistrict, Pulang Pisau Regency, during the 2024/2025 academic year. This experimental research employs two groups based on demographic location: urban (Group A) and rural (Group B). Each group is divided into experimental and control classes. Results show higher average mathematics achievement scores in experimental classes compared to control classes. Hypothesis testing yields: Group A (t-table = 0.680 > t-calculate = 0.547) and Group B (t-table = 0.690 > t-calculate = 0.033). Consequently, differentiated learning styles through PBL significantly enhance mathematics achievement among fourth-grade students